Data Management Strategy at Microsoft Best Practices from a Tech Giant's Decade-Long Data Transformation Journey - Plotnikovs, Aleksejs (Packt Publishing, Limited, 2024)
Leverage your data as a business asset, from readiness to actionable insights, and drive exceptional performance Key Features Learn strategies to create a data-driven culture and align data initiatives with business goals Navigate the ever-evolving business landscape with a modern data platform and unique Data IP Surpass competitors by harnessing the true value of data and fostering data literacy in your organization Purchase of the print or Kindle book includes a free PDF eBook Book Description Microsoft pioneered data innovation and investment ahead of many in the industry, setting a remarkable standard for data maturity. Written by a data leader with over 15 years of experience following Microsoft's data journey, this book delves into every crucial aspect of this journey, including change management, aligning with business needs, enhancing data value, and cultivating a data-driven culture. This book emphasizes that success in a data-driven enterprise goes beyond relying solely on modern technology and highlights the importance of prioritizing genuine business needs to propel necessary modernizations through change management practices. You'll see how data-driven innovation does not solely reside within central IT engineering teams but also among the data's business owners who rely on data daily for their operational needs. This guide empower these professionals with clean, easily discoverable, and business-ready data, marking a significant breakthrough in how data is perceived and utilized throughout an enterprise. You'll also discover advanced techniques to nurture the value of data as unique intellectual property, and differentiate your organization with the power of data. Its storytelling approach and summary of essential insights at the end of each chapter make this book invaluable for business and data leaders to advocate for crucial data investments. What you will learn Develop a data-driven roadmap to achieve significant and quantifiable business goals Discover the ties between data management and change management Explore the data maturity curve with essential technology investments Build, safeguard, and amplify your organization's unique Data Intellectual Property Equip business leaders with trustworthy and high value data for informed decision-making Unleash the value of data management and data governance to uplift your data investments Who this book is for This book is for data leaders, CDOs, CDAOs, data practitioners, data stewards, and enthusiasts, as well as modern business leaders intrigued by the transformative potential of data. While a technical background isn't essential, a basic understanding of data management and quality concepts will be helpful. The book avoids twisted technical, engineering, or data science aspects, making it accessible and insightful for data engineers and data scientists to gain a wider understanding of enterprise data needs and challenges.
Description based upon print version of record
Keywords: Database management; Business -- Data processing -- Management; Bases de données; Gestion; Gestion; Informatique; Gestion